THE EFFECT OF WATER-SOLUBLE SALTS ON THE MOISTURE REGIME OF SEALING STRUCTURES (Eureka Journal of Civil, Architecture and Urban Studies, 2025)
This article examines the calculation of the moisture regime in building envelope structures under the influence of water-soluble salts. Existing methods for assessing moisture conditions are analyzed, highlighting their limitations in aggressive environments where salts alter vapor permeability and sorption processes. The study focuses on lightweight expanded clay aggregate concrete panels and evaluates the effectiveness of organosilicon hydrophobizing additives (sodium ethylsiliconate (ESNK) and polyphenyl-ethoxysiloxane (FES)) in enhancing durability and thermophysical properties. Results indicate that these additives improve resistance to salt-induced moisture accumulation and corrosion.
Keywords: building envelope structures, moisture regime, water-soluble salts, vapor permeability, sorption processes, hydrophobizing additives, aggressive environments, lightweight concrete.